Identities in crisis in Iran politics, culture, and religion - Cohen, Ronen (Lexington Books, 2015)
Identities in Crisis in Iran aims at finding answers to the questions about the puzzling character of the Iranian identity. This book addresses the tension many Iranian people face that lie between the Persian culture and the Shi?a religion, women versus men, and culture versus traditions.